Generation Pep – study protocol for an intersectoral community-wide physical activity and healthy eating habits initiative for children and young people in Sweden - Leijon, Matti; Algotson, Albin; Bernhardsson, Susanne; Ekholm, David; Ersberg, Lydia; Höök, Malin J-son; Klüft, Carolina; Müssener, Ulrika; Garås, Elisabeth Skoog; Nilsen, Per (Frontiers in Public Health, 2024)
There is overwhelming evidence for the preventive effects of regular physical activity and healthy eating habits on the risk of for developing a non-communicable disease (NCD).Increasing attention has been paid to community-wide approaches in the battle against NCDs.Communities can create supportive policies, modify physical environments, and foster local stakeholder engagement through intersectoral collaboration to encourage communities to support healthy lifestyles. The Pep initiative is based on intersectoral community-wide collaboration amongst Sweden's municipalities. Primary targets are municipality professionals who work with children and young people as well as parents of children <18 years. The goal is to spread knowledge and create commitment to children's and young people's health with a special focus on physical activity and healthy eating habits to facilitate and support a healthy lifestyle. The overarching aim of the research project described in this study protocol is to investigate factors that influence the implementation of the Pep initiative in Sweden, to inform tailored implementation strategies addressing the needs and local prerequisites of the different municipalities.The project includes a qualitative and a quantitative study and is framed by a theoretical model involving four complementary forms of knowledge, explicitly recognised in the Pep initiative: knowledge about the issue; knowledge about interventions; knowledge about the context; and knowledge about implementation.Study 1 is a focus group study exploring barriers and facilitators to for implementing the Pep initiative. The study will be carried out in six municipalities, selected purposively to provide wide variation in municipality characteristics, including population size and geographical location. Data will be analysed using thematic analysis.Study 2 is a cross-sectional web-based survey investigating the implementability of the Pep initiative in Sweden's 290 municipalities. Conditions for implementing different areas of the Pep initiative will be examined in terms of the acceptability, appropriateness, and feasibility, three predictors of implementation success. Data will be analysed using non-parametric statistics.The findings of the two studies will increase understanding of the prerequisites for implementing the Pep initiative in Swedish municipalities, which will provide valuable input into how implementation of the Pep initiative can best be facilitated in the different municipality settings.